Wesoły autobus. (Koszalin : [s.n.], 1966)
Afisz inf. o przedstawieniu w Hali Stoczni Gdańskiej 21.11.1966 r.
Keywords: Stocznia Gdańska -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie artystyczne